Effect of Root Dentin Pretreatment on Micro-Push-Out Bond Strength of Fiber Posts to Root Canal Dentin: Cold Atmospheric Argon Plasma (CAAP) and Ethylenediaminetetraacetic Acid (EDTA) - Farzaneh Sadeghi Mahounak; Mahdi Abbasi; Naghmeh Meraji; Maryam Rezazadeh Sefideh; Mohammad Javad Kharrazi Fard; Elham Ahmadi; Ladan Ranjbar Omrani (International Journal of Dentistry)
Purpose. Debonding from the root canal dentin is the most common failure mode of fiber posts. This study aimed to assess the effects of cold atmospheric argon plasma (CAAP) and ethylenediaminetetraacetic acid (EDTA) on micro-push-out bond strength of fiber posts to root canal dentin. Materials and Methods. Forty maxillary canine teeth were decoronated, underwent endodontic treatment, and were stored in an incubator for 7 days. After post space preparation, the teeth were randomly divided into four groups for different surface treatments: (I) saline, (II) 17% EDTA, (III) CAAP, and (IV) 17% EDTA + CAAP. Fiber posts (Whitepost no. 2, FGM) were cemented into the root canals using Panavia F2.0 resin cement, and 1 mm-thick sections were made at the coronal, middle, and apical thirds of the roots. The samples underwent micro-push-out bond strength test. The mode of failure was also determined under a stereomicroscope. Data were analyzed using three-way ANOVA and Tukey’s post hoc test (α = 0.05). The mode of failure data were analyzed using the chi-square test. Results. The mean micro-push-out bond strength of fiber posts was not significantly different in the four groups (P>0.05). However, the bond strength values in the coronal third were significantly higher than the corresponding values in the apical third (P=0.01). There was no significant difference in the modes of failure between the groups (P>0.05). Conclusion. Application of CAAP alone or in combination with 17% EDTA could not successfully increase the bond strength of fiber posts to root canal dentin.